A Novel Heterozygous Mutation in the T-box Protein 4 Gene in an Adult Case of Small Patella Syndrome - Oda, Tomoyuki (J Orthop Case Rep, 2018)
INTRODUCTION: Small patella syndrome (SPS) is a rare skeletal dysplasia relating to the T-box protein 4 (TBX4) gene, which regulates the development of lower extremities. Patients typically present with recurrent patellar dislocation (RPD) in childhood or adolescence, leading to a diagnosis of SPS and subsequent treatment to improve activity levels. However, those with mild symptoms may not be diagnosed when young and present later after skeletal maturation, which might compromise treatment options. Further understanding of genetic mutations of SPS could possibly help early diagnosis and following adequate surgical treatment. In this case report, we present a surgically treated adult female case of RPD associated with SPS, carrying a novel heterozygous mutation in the TBX4 gene. CASE REPORT: A 19-year-old female presented with persistent right knee pain after an atraumatic episode ofpatellar dislocation during walking. The patient had a history of recurrent patella instability of the right knee with an onset at the age of 8 years due to a minor trauma. Patellar apprehension sign was positive bilaterally. There was radiological evidence of bilateral small patellae, hypoplastic femoral trochlea, and tibial tuberosity. A direct sequencing of the coding regions in the TBX4 gene had confirmed the diagnosis of SPS. A novel heterozygous mutation (p.L39PfsX35) was found in the patient and her father. Surgical treatment was indicated and the patient underwent an isolated medial patellofemoral ligament (MPFL) reconstruction while no distal realignment osteotomy was performed due to hypoplastic tibial tuberosity. Excellent subjective and objective outcomes were obtained at 1 year postoperatively. DISCUSSION: To the best of our knowledge, this is the first reported SPS case with a novel mutation in the TBX4 gene in an Asian population. While a satisfying short-term outcome was obtained by an isolated MPFL reconstruction, early genetic diagnosis in childhood with adequate surgical treatment (e.g., Roux-Goldthwait procedure) would be ideal considering the limited treatment options in skeletally matured patients. The reported case has added one mutation variant of the TBX4 gene, which may help prevent delays in diagnosis of SPS.